Radiosonde Observations of a Wintertime Meridional Convergence of Gravity Waves Around 60°S in the Lower Stratosphere. Issue 20 (20th October 2020) - Moffat‐Griffin, T.; Colwell, S. R.; Wright, C. J.; Hindley, N. P.; Mitchell, N. J.
Abstract: Satellite observations show that there is a wintertime hotspot of gravity wave activity, located mainly over the ocean, around 60°S in the stratosphere. However, the sources of the gravity waves making up this hotspot are varied and complex and remain unclear. Here we use radiosonde observations from 11 Antarctic stations and selected small islands close to 60°S to examine the horizontal directional pseudo‐momentum flux and energy density distributions of upward propagating gravity waves in the lower stratosphere. This paper shows, for the first time, that short vertical wavelength gravity waves in the lower stratosphere clearly propagate meridionally toward 60°S during the winter months. This result supports previous studies that show that this belt of gravity wave activity over the ocean is contributed to by wave sources outside 60°S. Plain Language Summary: Atmospheric gravity waves are buoyancy waves, where the restoring force is gravity, which can have horizontal wavelengths from a few tens to hundreds of kilometers. They can be generated by a variety of sources including wind flow over mountains and storms. Over the Drake Passage and out to the east around 60°S, a large hotspot of gravity waves has been observed in the wintertime stratosphere using satellite observations. The sources for this gravity wave hotspot are unclear as it mainly located over the open ocean. In this paper radiosonde observations are used to examine, for the first time, the directional variation in short vertical wavelength gravity waves close to 60°S in the lower stratosphere. It is found that during the winter months there is a meridional convergence of gravity waves toward 60°S, implying that the gravity wave sources of the hotspot are in fact be outside this region. Key Points: This paper provides evidence of a winter time convergence of gravity waves and their momentum flux toward 60°S This is the first time this has been observed for short vertical wavelength waves in the lower stratosphere